THE EFFECT OF LEADERSHIP, SALARY AND BENEFITS ON EMPLOYEE LOYALTY IN EXPORT IMPORT COMPANIES - Rika Fitri Ramayani; Romsa Endrekson; Heru Purnomo; Arman Syah Putra; Brian Givan (Journal of Innovation Research and Knowledge, 2022)
The background of this research is how to find out the influence of salary and allowance leadership on the loyalty of employees at import-export companies. With the influence of these variables, it can be seen what deficiencies can be improved. Development of the times and have loyal employees. The method used in this research is quantitative method and surveys 100 employees at import export companies, so that using this method will produce accurate and real data in the field. The problem raised in this research is how to find out the relationship between salary leadership and benefits on employee loyalty in an export-import company so that it can find the weak points of employees so that employee loyalty can be improved and can be improved. The purpose of this study is to find out the weaknesses of the variables that exist in an import-export company with these variables, it can be improved and can be developed continuously in order to increase employee loyalty and make the company progress and develop.